Characterising flavour differences in Mandarin fish muscle under live prey and formulated feed diets using flavouromics and metabolomics - Yang Cheng; Junjian Dong; Hetong Zhang; Yuan Zhang; Fengying Gao; Fubao Wang; Ziyang Wang; Xing Ye; Chengbin Wu; Chengfei Sun (Food Chemistry: Molecular Sciences)
Substituting formulated feed for trash fish in aquaculture has the potential to reduce farming costs and decrease dependence on natural resources. However, the impact of such feed substitution on muscle flavour remains unclear. This study is the first to utilise two-dimensional gas chromatography coupled with time-of-flight mass spectrometry (GC × GC-TOF MS) and liquid chromatography–mass spectrometry (LC-MS) to analyse differences in muscle flavour between mandarin fish (Siniperca chuatsi) fed live prey and those fed formulated feed. The results identified 65 differential flavour compounds, with four key contributors: 2,3-butanedione, (E)-2-nonenal, furan, 2-pentyl-, and (E)-2-octenal. Metabolomic analysis revealed 139 differential metabolites, with significant upregulation of amino acid metabolites such as threonine and L-homoserine in the muscle of fish fed formulated feed. KEGG pathway enrichment highlighted glycine, serine and threonine metabolism, and aminoacyl-tRNA biosynthesis as critical pathways. Correlation analysis demonstrated significant associations between precursors like dihydroxyacetone phosphate and O-phosphoserine and key flavour compounds. The findings indicate that mandarin fish fed live prey exhibited a more pronounced nutty, buttery, ham-like aroma alongside a fresh, grassy scent, whereas those fed formulated feed showed a diminished earthy off-flavour. Dihydroxyacetone phosphate, L-homoserine, threonine, and linoleic acid were identified as important flavour precursors. Overall, these findings provide a theoretical basis for optimising the muscle flavour of mandarin fish in feed-based aquaculture.